Transparent Cross-Flow Platform as Chemiluminescence Detection Cell in Cross Injection Analysis - Thachkorn Somboonsuk; Phoonthawee Saetear; Thitirat Mantim; Nuanlaor Ratanawimarnwong; Prapin Wilairat; Nathawut Choengchan; Duangjai Nacapricha (Molecules, 2023)
. The precision was ≤4.2% RSD. The consumption of the samples and reagents was ca. 170 µL per analysis cycle.
Keywords: Analytical chemistry methods development; Electrochemical sensors and biosensors; Electrochemical Analysis and Applications